Adult Learning in Canada in an International Perspective - Kjell Rubenson (Adult Education Research Conference, 2007)
This paper examines adult learning in Canada in an international perspective. The paper explores the level of inclusiveness and observes the relative importance of the state, employer and individual in the structuring of learning opportunities.